QUANTITATIVE MICROSCOPY METHODS APPLIED TO THE STUDY OF VAGINAL SECRETIONS - Gordillo Delboy, R. (2015)
A method of quantitative microscopy applied to the study of exfoliated cells from the vaginal secretion during a normal menstrual cycle develops. The method is based on determining the relationship cyto-core plasma by comparing surface modules. The technique is simple. The preparations were observed in flask with phase contrast microscope. It does not require particular coloration. Counting modules surface it is made by the camera lucida. Analytically it demonstrated that cytoplasmic core ratio is a measure of cell growth and division and its variation defines fundamental properties of the vaginal and sexual cycle. Limitations of the method are discussed.